2020
DOI: 10.1021/acs.jpcb.0c03359
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effects of an Antifungal Moiety and DMSO on Pore Formation over Lipid Membranes Revealed by Free Energy Calculations

Abstract: Itraconazole is a triazole drug widely used in the treatment of fungal infections, and it is in clinical trials for treatment of several cancers. However, the drug suffers from poor solubility, while experiments have shown that itraconazole delivery in liposome nanocarriers improves both circulation half-life and tissue distribution. The drug release mechanism from the nanocarrier is still unknown, and it depends on several factors including membrane stability against defect formation. In this work, we used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 82 publications
(186 reference statements)
2
16
1
Order By: Relevance
“…The free energy barrier is reduced when a larger number of peptides is present in the bilayer and almost disappears, i.e., is close to 0 kJ/mol, when six peptides are present in the membrane. Atomistic MD simulation studies have also found that synthetic polycations [834], itraconazole [258], and DMSO [258] induce a decrease in the free energy barrier against pore nucleation. [832].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 97%
See 2 more Smart Citations
“…The free energy barrier is reduced when a larger number of peptides is present in the bilayer and almost disappears, i.e., is close to 0 kJ/mol, when six peptides are present in the membrane. Atomistic MD simulation studies have also found that synthetic polycations [834], itraconazole [258], and DMSO [258] induce a decrease in the free energy barrier against pore nucleation. [832].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 97%
“…Levofloxacin [236][237][238], Clarithromycin [236], Isoniazid N -acylated derivatives [239], Rifampicin [234,240], Mangostin [241], Trimethoprim [242], Negamycin [243] Potential antibiotic Kanamycin A [133], nTZDpa and its derivatives [244], Cholic acid derived amphiphiles [245], γ-terpineol [246], Bithionol [247] Antimicrobial compound Chlorhexidine [248][249][250], Triclosan [251], Octenidine [250] Antiparasitic Praziquantel [252] Antiviral drugs Darunavir [253], Amantadine [254][255][256], Spiro[pyrrolidine-2,2 -adamantane] [254,255], 20,30-dideoxyadenosine (Didanosine) [242], Saffron [257] Antifungal drug Itraconazole, [184,186,187,258], Nystatin [259], Amphotericin B [260] Rheumatoid arthritis Lapatinib [213] Nonsteroidal antiinflammatory drugs, inhibitor of cyclooxygenase-1 and -2…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steps during pore formation mediated by the insertion and aggregation of peptides were described by unbiased molecular dynamics (MD) simulations [27][28][29]. The energetic cost of formation of pores has also been quantified in allatom MD simulations [30,31], for distinct lipid types [32] and also in the presence of solutes [33][34][35], as well as in coarse-grain simulations [36]. These simulations revealed the existence of metastable states during pore formation, which were tightly linked to the hydrophilic head-hydrophobic tail volume ratio [32].…”
mentioning
confidence: 99%
“…Understanding the mechanism of translocation and binding of a variety of drugs, transfection reagents, and antifungal/ antimicrobial compounds also remains a hot topic, 17,18 with additional complexity arising from the presence of certain lipids, 19 synergetic effects, 20 and modulation of pH. 21,22 Apart from these more applied studies, this Virtual Special Issue includes exciting contributions aimed at increasing our understanding of fundamental physical mechanisms that govern membrane behavior.…”
mentioning
confidence: 99%